Existence and continuous dependence of solution of the Boussinesq wave equation in periodic Sobolev spaces - Papuico Bernardo, Victor (2020)
We will begin our study, focusing on the theory of periodic Sobolev spaces, for this we cite [1]. Then, we will prove that the non-homogeneous Boussinesq equation has a local solution and that the solution also continually depends on the initial data and non-homogeneity, we do this intuitively using Fourier theory and in an elegant version introducing families of strongly continuous operators, inspired by the work of Iorio [1], Santiago and Rojas [4], [3] and [2].